Business Opportunity from Hydroponics: A Research on Community Service Angle - Nasrudin, Nasrudin; Bahtiar, Yusuf; Pratiwi, Erza Harum (Jurnal Abdimas, 2023)
Hydroponics is agricultural cultivation without using soil, so this hydroponic farming system does not require a large area of land for its implementation. Hydroponic plants nowadays are very useful, especially after the pandemic because during the pandemic, the economy is declining, and growing hydroponics is one way to support economic needs. The aim of this research was to develop the potential of natural and economic resources in the surrounding environment and to find out the factors causing the local community's lack of understanding of hydroponics. This research was a community service angle. The method in this research was a descriptive qualitative method. collecting data using interview methods and documentation. The results of the research show that there are still many people who lack information about hydroponic plants, so this is one of the factors preventing hydroponics from developing.